ANALISIS KESETARAAN GENDER DALAM PENGUATAN KELEMBAGAAN UNIVERSITAS HALU OLEO - Hasan, Abdul; Matoka, Ulfa (JURNAL EKONOMI UHO, 2016)
This study aimed to obtain information on gender equality in Haluoleo University. Secondary data were obtained from the Personnel and Finance Board across the Faculty/Program and Technical Services Unit-Information Technology Haluoleo University in 2015 period. The research used Gender Analysis Pathway. The result show that Halu Oleo University have gender bias. The rate of participation and access of men higer than women in the institutional elements such as students, official structurally of faculty and administrative staff, except for Faculty of Pharmacy and Public Health Faculty.